Pengembangan Sumber-Sumber Pembelajaran Bahasa Arab: Telaah Epistemologi Pemikiran Filsafat Empirisme George Berkeley - Muhammad Rusydi; Abd. Muis Said; Muhammad Amin Sahib; Rosbiah Machmuddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
This article focuses on examining the Development of Arabic Learning Resources: An Epistemological Review of George Berkeley's Empiricism Philosophy. Through literature research, it was found that Arabic learning resources are one of the important factors in improving students' language skills. Their development is not just about providing materials but also creating learning experiences that allow students to gain knowledge through direct interaction with objects and phenomena around them. George Berkeley's thinking emphasizes the importance of perception in the formation of knowledge, so the richness of perceptual experiences with learning resources can strengthen the understanding of Arabic in a concrete and meaningful way. Thus, contextual learning resources help learners connect Arabic material with real-life experiences, daily life, and their social environment, making learning more practical, relevant, and easy to understand.